Making Employee Loyalty: Impact Of Leadership And Job Satisfaction - Rizky Maulana; Raghief El Hida; Moh. Fahri Ramdani; Sunimah, Sunimah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study aims to analyze and determine the influence of leadership and job satisfaction on employee loyalty at PT Toyamilindo Cirebon Regency. The research method used is quantitative. The population of this study is employees of PT Toyamilindo Cirebon Regency which amounts to 100 people. The sample in this study amounted to 100 people using the saturated sample method. Data collection is carried out by giving questionnaires to employees at PT. Toyamilindo, Cirebon Regency. The data analysis techniques used are descriptive analysis and multiple linear regression analysis. Partial results show that job satisfaction variables have a positive and significant effect on employee loyalty. While the leadership variable has a positive and insignificant influence. These results show that job satisfaction has a significant effect on employee loyalty to PT employees. Toyamilindo, Cirebon Regency.